DESIGN OPTIMIZATION FOR RELIABILITY OF THE AIR BRAKING SYSTEM FOR LRT JABODEBEK USING GENETIC ALGORITHM - Rahmania Warda, Sovia
The pneumatic braking system is a crucial part in determining the safety performance of a train system in general, and the Jabodebek Light Rail Transit (LRT) in particular. In line with the development of technology and public services, manufacturers of railway rolling stock are faced with the challenge of providing products with a certain level of reliability. Therefore, reliability aspects need to be considered since the product design phase, especially in the selection of components from vendors in the braking system. This thesis aims to provide recommendations for the selection of LRT braking system components based on reliability and cost criteria using genetic algorithms. The method used in this reliability analysis begins with data collection in the form of asset data, failure data, piping diagrams, product manuals, and system descriptions. Asset data collection is carried out while determining the systems, subsystems, and components of the Jabodebek LRT air braking system to be analyzed. Furthermore, the creation of Product Breakdown Structure (PBS), Functional Block Diagram (FBD), and Reliability Block Diagram (RBD) modelling for the four main functions of the braking system. The design for reliability is carried out with an optimization process using genetic algorithms to maximize reliability and minimize the total purchase cost from the initial design conditions. The results obtained are the reliability value of the Jabodebek LRT air braking system within 2 months (1000 hours) which is 84.4%, the probability of failure is 15.6%, the failure rate is 1.69E-04 per hour, and the average time between failures is 5,903 hours and the reliability value is successfully optimized by providing recommendations for optimal vendor selection to 91%. This recommendation also succeeded in reducing the total braking system procurement cost by Rp3,500,000, from Rp2,666,438,400 to Rp2,662,938,400.